The elasticity of taxable income of high earners: Evidence from Hungary - Áron Kiss; Pálma Mosberger (Magyar Nemzeti Bank, 2011)
The paper studies how high-income taxpayers responded to the introduction of the 'extraordinary tax on individuals' in Hungary in 2007. The study is based on a panel of tax returns compiled by the Hungarian Tax Authority for the purposes of this study, containing information on 10 percent of tax-filers from 2005 and three subsequent years. We estimate the elasticity of taxable income with respect to the marginal net-of-tax rate and find that the taxable income of Hungarian high earners is moderately responsive to taxation: the estimated elasticity is about 0.2. This means that if the upper tax rate of the 2010 Hungarian tax system were increased by a small amount, the behavioral response of taxpayers would reduce the additional tax revenue by about 60 percent. We find evidence suggesting that the elasticity is a reflection of a labor supply response to the tax change on the intensive margin, and not a reflection of tax shifting, avoidance or evasion.
Keywords: H20; H24; H31; J22; 330; taxable income elasticity; personal income tax; tax avoidance